Assessing negative thermal expansion in mesoporous metal–organic frameworks by molecular simulation. Issue 41 (13th September 2019) - Evans, Jack D.; Dürholt, Johannes P.; Kaskel, Stefan; Schmid, Rochus
Abstract : Molecular simulations reveal that mesoporous metal–organic frameworks display large volumetric negative thermal expansion, which has a considerable effect on mechanical stability, outlining an alternative application for these ultra-porous materials. Abstract : Most conventional materials display expansion in response to heating, so there is considerable interest in identifying materials that display the opposite behavior, negative thermal expansion (NTE). The current study investigated the temperature-induced contraction of seven mesoporous metal–organic frameworks (MOFs) of varying topology and composition, which exhibit outstanding porosity, using molecular simulation. We found exceptional NTE for the most porous MOFs, as well as a correlation between the coefficient of NTE and porosity. The large molecular subunits of the MOFs were further studied to find they intrinsically display NTE, corresponding to terahertz vibrational modes. As a result, NTE has a considerable effect on the mechanical properties of these MOFs and is an important consideration for understanding the mechanical stability of new extremely porous materials.